Murabahah Bil Wakalah Agreement at Bank Aceh Syariah: a Study of Used Car Ownership Finance - Wahyudani, Zulham; Zulhilmi, Zulhilmi (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2023)
This paper aims to analyze the practice of murabahah contracts at Bank Aceh Syariah Langsa. So far, the paradigm for developing car ownership financing contracts has been the use of Murābahah contracts. In practice, banks often give customers money instead of cars, not in accordance with previously understood contracts, this becomes a dilemma for customers because in conditions like this, the inclusion of a wakalah contract which is part of the tabaru' contract to apply for financing at Bank Aceh Sharia. This research is included in non-doctrinal research with a conceptual approach. The context approach is used to analyze theoretically and practically related to the use of murabahah contracts. The research results show that Bank Aceh Syariah Langsa has not used a murabahah contract, this is because; first, the bank does not have sufficient expertise or experience in buying and selling cars; second, the tendency of customers and banks to use wakalah contracts as mandates for customers who want to buy a car. third, the banking sector does not have in-depth knowledge about the type of car, car price, car condition, or the legality of the customer's car transaction. Because the bank has handed over money to the customer to pay for the car to the seller. This article contributes to the importance of customer and bank understanding of the murabahah bil wakalah contract which requires collaboration between the bank, the seller and the customer for the monitoring process in purchasing a car to avoid conditions and gharar in buying and selling transactions. Because banks are not institutions that exclusively focus on buying and selling activities.